Factors associated with measles vaccine immunogenicity in children at University Teaching Hospitals, Lusaka, Zambia. - Priscilla Nkonde Gardner; Jimmy Hangoma; Cephas Sialubanje; Musole Chipoya; Lillian Lamba; Musaku Mwenechanya; Rodgers Chilyabanyama; Mpanga Kasonde; Davie Simwaba; Muzala Kapina; Soo Young; Kelvin Mwangilwa; et al. (PLOS Global Public Health)
Measles poses a significant global public health challenge, particularly in low-resource settings where vaccination coverage is limited. This study examined factors associated with measles vaccine immunogenicity in children aged 2-15 years at the University Teaching Children's Hospital and the HIV Pediatric Centre of Excellence in Lusaka, Zambia. This comparative analytical cross-sectional study was conducted from April to July 2024, enrolling 200 children, including 100 HIV-positive and 100 HIV-negative participants. All children had received at least two doses of a measles-containing vaccine and had no history of measles infection in the past six months. Blood samples were analyzed for measles immunity, while data on age, HIV status, breastfeeding history, and socio-demographic factors were collected. Among HIV-negative children, 75% retained immunity, whereas only 38% of HIV-positive children retained immunity. Multivariate logistic regression showed that children aged 10-15 years were less likely to retain immunity compared to those aged 2-4 years (AOR = 0.270, 95% CI [0.114-0.618], p = 0.002). HIV-positive children had lower odds of retaining immunity compared to HIV-negative children (AOR = 0.290, 95% CI [0.137-0.594], p < 0.001). Breastfed children had higher immunity retention (AOR = 0.336, 95% CI [0.147-0.738], p = 0.007) compared to non-breastfed children. Residing in Lusaka was associated with lower immunity retention (AOR = 0.250, 95% CI [0.066-0.859], p = 0.031). These findings highlight the protective role of breastfeeding and suggest that older and HIV-infected children may benefit from booster doses to sustain measles immunity.